Learning Arabic Language Skills for Adults (Jack C. Richard Thought Review) - Iis Susiawati Abdullah; Dadan Mardani Samsudin (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2022)
Richards' thoughts on language learning are indeed very interesting to study. According to Richard on receptive language skills, there are three methods: Oral Approach and Situational Language Teaching, Audiolingual Method and The Silent Way. The approach of this study is literature from several sources related to the relevant discussion. The author uses the text study method in analyzing the collected data with the aim of describing the content clearly and in detail and aiming to reveal the concept of Jack C. Richard's thinking in learning receptive language skills and knowing the right receptive learning concept in learning receptive Arabic skills in adult education. The results of this study found that Jack C Richard's thoughts can be applied to adult education, especially in learning receptive Arabic skills by adjusting the conditions and situations that exist in the material and adult learners.